Challenges faced by women in Medical Education and Trainings - Farooq, Zainab; Shabbir, Noor Zehra (Annals of King Edward Medical University, 2024)
The development of a nation's health care system depends heavily on medical education and training. Like many other places in the world, Pakistan has historically had a male-dominated medical profession. But the number of women choosing jobs in medicine has increased commendably in recent years. Despite this encouraging development, Pakistani women still encounter many obstacles throughout their pursuit of medical education and training, which may impede their ability to advance professionally and make a contribution to the healthcare industry. Globally, female healthcare employees still have a lot of obstacles to overcome at work, including gender inequality, weak human resource policy, and family responsibilities that limit their ability to advance professionally. Work-family harmony has been cited in many nations as a substantial roadblock to career progress.In addition to unequal compensation, bad working conditions, little prospects for career advancement, work-related stress, and unfavourable policies that support patriarchy, women in the health sciences also confront issues connected to poor work environments. And in our paper, this issue will be underlined.[1]